The Effect of Muscle Electrical Stimulation on Muscle Stiffness Problems and Musculoskeletal Pain Caused by Muscle Imbalance: A Systematic Review - Saatchian, Vahid; Türkmen, Mutlu; Esfahani, Mahdi; Amin Zadeh, Reza; Talib, Ahmed Mushtaq; Azimkhani, Amin (Progress in Nutrition, 2021)
Whole Body Electrical Stimulation (WB-EMS) is a relatively new training method that has been used extensively in recent years, however, the lack of consensus on the efficacy of Whole Body Electrical Stimulation exists, and the aim of this study is to investigate the effects of this method on postural structure problems and musculoskeletal pain. Summary of articles by ISC,  Google Scholar , American Journal of Sports Medicine , PubMed Journal of Rehabilitation Medicine , Cochrane , and Sports Medicine Journals between 2000 and 2019 were studied to identify all studies that report electrical stimulation applied simultaneously to the upper and lower limbs.Keywords: Electrical stimulation, Electrical muscle stimulation, Functional electrical stimulation, Whole body electrical stimulation, Wearable sensors, Electrotherapy, Electrode vest, Electrode vest for treatment and rehabilitation, E-fit, Electronic muscle stimulation , Whole body electronic muscle stimulation, Electronic Stimulation, Electronic Suit, Wearable Sensor, and Electrotherapy were used to obtain relevant articles and finally, 22 articles were compared according to the set criteria of 107 papers.Based on the results of studies on the effects of Whole Body Electrical Stimulation, this tool is based on parameters such as muscle strength, muscle size, body composition, obesity, sarcopenia, sarcopenia-induced obesity and pain reduction in non-specific chronic low back pain patients, have a significant positive effect.Due to the lack of studies on the effects of Whole Body Electrical Stimulation and the inconsistency between studies and the lack of similar consensus, further research is needed.